Research Progress of Antibody–Drug Conjugate Therapy for Advanced Gastric Cancer - Wang, Na; Mei, Qingyun; Wang, Ziwei; Zhao, Lu; Zhang, Dou; Liao, Dongying; Zuo, Jinhui; Xie, Hongxia; Jia, Yingjie; Kong, Fanming (Frontiers in Oncology, 2022)
Gastric cancer is an intractable malignant tumor that has the fifth highest morbidity and the third highest mortality in the world. Even though various treatment options did much to ameliorate the prognosis of advanced gastric cancer, the survival time remained unsatisfactory. It is significant to develop new therapeutic agents to improve the long-term outcome. Antibody–drug conjugate is an innovative and potent antineoplastic drug composed of a specifically targeted monoclonal antibody, a chemical linker, and a small molecule cytotoxic payload. Powerful therapeutic efficacy and moderate toxicity are its preponderant advantages, which imply the inevitable pharmaceutical developments to meet the demand for individualized precision therapy. Nevertheless, it is unavoidable that there is a phenomenon of drug resistance in this agent. This article systematically reviewed the recent progress of antibody–drug conjugates in advanced gastric cancer therapy.